HATE CRIME AGAINST PEOPLE WITH DISABILITIES: A LEGAL AND SOCIOLOGICAL ANALYSIS OF THE CASE OF ‘VAQUEIRINHO,’ AN INTELLECTUALLY DISABLED PERSON KILLED BY A LIONESS IN THE ZOO: ANÁLISE SOCIOLÓGICA JURÍDICA DO CASO ‘VAQUEIRINHO’, PESSOA COM DEFICIÊNCIA INTELECTUAL MORTO POR UMA LEOA NO ZOOLÓGICO (ESMAT Magazine, 2026)
This study examines the case of “Vaqueirinho,” a young person with intellectual disability and severe mental suffering, who was killed by a lion at the Arruda Câmara Zoobotanical Park in João Pessoa, highlighting structural failures in public protection, mental health, and social inclusion policies. The objective is to understand how experiences of abandonment, hunger, abuse, and lack of institutional support constitute ongoing violations of rights guaranteed by the Brazilian Child and Adolescent Statute and the Statute of Persons with Disabilities. The methodology involves documentary analysis, literature review, and application of theoretical frameworks from Michel Foucault, Martha Nussbaum, Erving Goffman, and Boaventura de Sousa Santos, addressing disciplinary devices, criminalizing stigmas, and exclusionary practices that limit human dignity and capacities. The findings indicate that the zoo tragedy was not an isolated accident, but a predictable outcome of state negligence in site security and societal reactions that normalize violence against vulnerable individuals. The study concludes that the event reflects collective harm, legal and moral responsibility of the State, and underscores the urgent need for comprehensive care policies, effective protection, and institutional accountability.
Keywords: intellectual disability; human rights; mental health; public policy; social exclusion